2016
DOI: 10.5380/rf.v46i2.40866
|View full text |Cite
|
Sign up to set email alerts
|

PRODUÇÃO DE PAINÉIS AGLOMERADOS COM MISTURAS DE SEIS ESPÉCIES DE MADEIRAS DA AMAZÔNIA E Pinus taeda

Abstract: ResumoEste estudo teve como objetivo avaliar a qualidade de painéis aglomerados produzidos com misturas de seis espécies de madeiras tropicais da Amazônia e Pinus taeda. As espécies estudadas foram: Eschweilera odora, Byrsonima crispa, Swartzia recurva, Eschweilera coriacea, Manilkara amazonica e Pouteria guianensis. O plano experimental consistiu em mistura de três espécies tropicais e, mistura destas na proporção de 50% com Pinus taeda. Foram produzidos painéis experimentais com densidade nominal de 0,75 g/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Regarding the results presented, the perpendicular tensile strength varied between 0.63MPa (NI) to 0.95MPa (Diniziaexcelsa Ducke, 85%), thus meeting the minimum requirement of ANSI A208.1 [CPA, 2009] and classifying them as a utility in an industrial environment. [Negrão et al, 2014] in their study finds an average value of 1.17MPa, while [Iwakiri et al, 2016] that addresses values of 0.75Mpa to 0.90MPa. Despite this, these values are lower than those found by [Surdi, Bortoletto Junior & Castro, 2018] of 1.16MPa and 1.61MPa.…”
Section: Mechanical Propertiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Regarding the results presented, the perpendicular tensile strength varied between 0.63MPa (NI) to 0.95MPa (Diniziaexcelsa Ducke, 85%), thus meeting the minimum requirement of ANSI A208.1 [CPA, 2009] and classifying them as a utility in an industrial environment. [Negrão et al, 2014] in their study finds an average value of 1.17MPa, while [Iwakiri et al, 2016] that addresses values of 0.75Mpa to 0.90MPa. Despite this, these values are lower than those found by [Surdi, Bortoletto Junior & Castro, 2018] of 1.16MPa and 1.61MPa.…”
Section: Mechanical Propertiesmentioning
confidence: 87%
“…Chevalier treatments and the mixed treatment of high-density commercial Amazonian species (p0.05). In the evaluation carried out in the twenty-four hour period, there was no effect on the treatments and the absorption of the panels (X² (2) = 5.84; p> 0.05 9.35% for twenty-four hours, while [Iwakiri et al, 2016] working with agglomerated panels of Amazonian species presents values ranging from 2.67% to 7.67% for two hours and 8.44% to 18.50% for twenty-four hours.…”
Section: Absorption and Swellingmentioning
confidence: 93%
“…The percentage is still below the production possibilities of Brazilian industries, considering the country's timber potential and installed technologies (Nogueira et al, 2018). The main industries of agglomerated panels which supply the main furniture centers are in the South and Southeast Regions, located in the states of São Paulo, Minas Gerais, Paraná, Santa Catarina and Rio Grande do Sul (Iwakiri et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the use of alternative wood species, such as tropical species, can be an alternative in the production of OSB panels, as long as they are mixed with other species of lower density [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In some timber sectors, between 30% and 70% of the volume of roundwood harvested is converted into waste [19,20]. Therefore, the use of residues from the primary and secondary processing of tropical wood and the study of these species in panel production can provide subsidies for the installation of OSB factories in the Amazon region [18]. As an example, a study carried out using tropical wood residues demonstrated the potential use of residues for non-structural purposes, furniture, tools, and panels composed of short pieces [21].…”
Section: Introductionmentioning
confidence: 99%